Stimulated emission and coherent control of gamma photons described by quantum mechanical model - Michal Hausner; Vít Procházka; Vlastimil Vrba (Physical Review Research)
Creating a coherent source of gamma radiation remains one of the biggest motivations in gamma-ray optics. Such a source would utilize the stimulated emission of gamma photons. However, to achieve lasing in the high-energy regime other physical principles such as the lasing without inversion are needed to be explored. One of the currently developed approaches uses coherent control of gamma radiation waveforms to induce transparency in a medium by applying ultra-acoustic vibrations. In this paper a theoretical description of the stimulated emission and coherent control of gamma rays is developed on the basis of a one-dimensional quantum mechanical formalism. The model of the gamma radiation coherent control shows a good agreement with the conventional semiclassical description of the phenomenon. The model of the stimulated emission was developed with the assumptions which enable to propose a specific experimental arrangement for simultaneous detections of pairs of gamma photons. This proposal is further discussed in the context of the experimental observation of the stimulated emission of gamma photons.